Kejahatan Dan Hukuman: Tantangan Filosofis Determinisme-Kausal Terhadap Pertanggungjawaban - Kabir, Syahrul Fauzul (UI Scholars Hub, 2019)
The existence of free will is required to legitimize criminal responsibility both legally and morally. Criminal responsibility, which was constructed through the concepts of actus reus and mens rea (cartesian-dualism) has been questioned by causal-determinism. As through these concepts moral responsibility and criminal practices, philosophically, are legitimized. Determinism, as a comprehensive worldview, closes the possibility of free will's existence. Contemporary science's findings in the fields of genetics, psychology, and neuroscience are increasingly verifying the determinism's thesis, rather than falsifying it. The law's concept embraces folk-psychology in which every actions are weighed ethically even by those who believe in causal-determinism. The concept of responsibility and punishment is the social practice required by society for the sake of order, utility and legal certainty. The objective of punishment is not only based on the retributive justice's concept, but also hold the utility principle that is consequentialist; Punishment creates deterrent effect and order.